The Implementation of Mind Mapping Technique in Improving Students’ Writing Skill at SMA Negeri 2 Ambon - Nahuway, Vivian; Gaspersz, Merylin B. A.; Latuheru, Henry (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2024)
This research is focused on the implementation of mind mapping technique in improving students’ writing skill. This research is aimed to describe the improvement of students’ writing skill by implementing mind mapping technique and to see the students’ response towards the implementation of mind mapping technique. Mind mapping can simply define as a creative technique involving lines, colors, keywords, and images which connected each other. The research design is classroom action research that consist of preliminary study and one cycle. There are four activities, there are planning, acting, observing, and reflecting. This research focus on report text materials and supporting instruments were used to help the researcher to collect and analyze the data such as questionnaire and test. The result of this research showed that students’ responses were positive for the implementation of mind mapping technique and this is also support by the post test of writing report text where most of students got high score above the criteria of minimum mastery (KKM).